6.35 Problems 3401 to 3500

Table 6.69: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

3401

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+\left (1+x \right ) y = x \left (x^{2}+x +1\right ) \]

3402

\[ {}\left (x^{3}+2 x^{2}\right ) y^{\prime \prime }-x y^{\prime }+\left (1-x \right ) y = x^{2} \left (1+x \right )^{2} \]

3403

\[ {}y^{\prime } = 2 \]

3404

\[ {}y^{\prime } = 2 \,{\mathrm e}^{3 x} \]

3405

\[ {}y^{\prime } = \frac {2}{\sqrt {-x^{2}+1}} \]

3406

\[ {}y^{\prime } = {\mathrm e}^{x^{2}} \]

3407

\[ {}y^{\prime } = x \,{\mathrm e}^{x^{2}} \]

3408

\[ {}y^{\prime } = \arcsin \left (x \right ) \]

3409

\[ {}y^{\prime } = x y \]

3410

\[ {}y^{\prime } = x^{2} y^{2} \]

3411

\[ {}y^{\prime } = -x \,{\mathrm e}^{y} \]

3412

\[ {}y^{\prime } \sin \left (y\right ) = x^{2} \]

3413

\[ {}x y^{\prime } = \sqrt {1-y^{2}} \]

3414

\[ {}{y^{\prime }}^{2}-y^{2} = 0 \]

3415

\[ {}{y^{\prime }}^{2}-3 y^{\prime }+2 = 0 \]

3416

\[ {}\left (x^{2}+1\right ) y^{\prime } = 1 \]

3417

\[ {}\sin \left (x \right ) y^{\prime } = 1 \]

3418

\[ {}y^{\prime } = t^{2}+3 \]

3419

\[ {}y^{\prime } = t \,{\mathrm e}^{2 t} \]

3420

\[ {}y^{\prime } = \sin \left (3 t \right ) \]

3421

\[ {}y^{\prime } = \sin \left (t \right )^{2} \]

3422

\[ {}y^{\prime } = \frac {t}{t^{2}+4} \]

3423

\[ {}y^{\prime } = \ln \left (t \right ) \]

3424

\[ {}y^{\prime } = \frac {t}{\sqrt {t}+1} \]

3425

\[ {}y^{\prime } = 2 y-4 \]

3426

\[ {}y^{\prime } = -y^{3} \]

3427

\[ {}y^{\prime } = \frac {{\mathrm e}^{t}}{y} \]

3428

\[ {}y^{\prime } = t \,{\mathrm e}^{2 t} \]

3429

\[ {}y^{\prime } = \sin \left (t \right )^{2} \]

3430

\[ {}y^{\prime } = 8 \,{\mathrm e}^{4 t}+t \]

3431

\[ {}y^{\prime } = \frac {y}{t} \]

3432

\[ {}y^{\prime } = -\frac {t}{y} \]

3433

\[ {}y^{\prime } = y^{2}-y \]

3434

\[ {}y^{\prime } = y-1 \]

3435

\[ {}y^{\prime } = 1-y \]

3436

\[ {}y^{\prime } = y^{3}-y^{2} \]

3437

\[ {}y^{\prime } = 1-y^{2} \]

3438

\[ {}y^{\prime } = \left (t^{2}+1\right ) y \]

3439

\[ {}y^{\prime } = -y \]

3440

\[ {}y^{\prime } = 2 y+{\mathrm e}^{-3 t} \]

3441

\[ {}y^{\prime } = 2 y+{\mathrm e}^{2 t} \]

3442

\[ {}y^{\prime } = t -y \]

3443

\[ {}t y^{\prime }+2 y = \sin \left (t \right ) \]

3444

\[ {}y^{\prime } = y \tan \left (t \right )+\sec \left (t \right ) \]

3445

\[ {}y^{\prime } = \frac {2 t y}{t^{2}+1}+t +1 \]

3446

\[ {}y^{\prime } = y \tan \left (t \right )+\sec \left (t \right )^{3} \]

3447

\[ {}y^{\prime } = y \]

3448

\[ {}y^{\prime } = 2 y \]

3449

\[ {}t y^{\prime } = y+t^{3} \]

3450

\[ {}y^{\prime } = -y \tan \left (t \right )+\sec \left (t \right ) \]

3451

\[ {}y^{\prime } = \frac {2 y}{t +1} \]

3452

\[ {}t y^{\prime } = -y+t^{3} \]

3453

\[ {}y^{\prime }+4 \tan \left (2 t \right ) y = \tan \left (2 t \right ) \]

3454

\[ {}t \ln \left (t \right ) y^{\prime } = t \ln \left (t \right )-y \]

3455

\[ {}y^{\prime } = \frac {2 y}{-t^{2}+1}+3 \]

3456

\[ {}y^{\prime } = -\cot \left (t \right ) y+6 \cos \left (t \right )^{2} \]

3457

\[ {}y^{\prime }-x y^{3} = 0 \]

3458

\[ {}\frac {y^{\prime }}{\tan \left (x \right )}-\frac {y}{x^{2}+1} = 0 \]

3459

\[ {}x^{2} y^{\prime }+x y^{2} = 4 y^{2} \]

3460

\[ {}y \left (2 x^{2} y^{2}+1\right ) y^{\prime }+x \left (y^{4}+1\right ) = 0 \]

3461

\[ {}2 x y^{\prime }+3 x +y = 0 \]

3462

\[ {}\left (\cos \left (x \right )^{2}+y \sin \left (2 x \right )\right ) y^{\prime }+y^{2} = 0 \]

3463

\[ {}\left (-x^{2}+1\right ) y^{\prime }+4 x y = \left (-x^{2}+1\right )^{{3}/{2}} \]

3464

\[ {}y^{\prime }-y \cot \left (x \right )+\frac {1}{\sin \left (x \right )} = 0 \]

3465

\[ {}\left (x +y^{3}\right ) y^{\prime } = y \]

3466

\[ {}y^{\prime } = -\frac {2 x^{2}+y^{2}+x}{x y} \]

3467

\[ {}\left (y-x \right ) y^{\prime }+2 x +3 y = 0 \]

3468

\[ {}y^{\prime } = \frac {1}{x +2 y+1} \]

3469

\[ {}y^{\prime } = -\frac {x +y}{3 x +3 y-4} \]

3470

\[ {}y^{\prime } = \tan \left (x \right ) \cos \left (y\right ) \left (\cos \left (y\right )+\sin \left (y\right )\right ) \]

3471

\[ {}x \left (1-2 x^{2} y\right ) y^{\prime }+y = 3 x^{2} y^{2} \]

3472

\[ {}y^{\prime }+\frac {x y}{a^{2}+x^{2}} = x \]

3473

\[ {}y^{\prime } = \frac {4 y^{2}}{x^{2}}-y^{2} \]

3474

\[ {}y^{\prime }-\frac {y}{x} = 1 \]

3475

\[ {}y^{\prime }-y \tan \left (x \right ) = 1 \]

3476

\[ {}y^{\prime }-\frac {y^{2}}{x^{2}} = {\frac {1}{4}} \]

3477

\[ {}y^{\prime }-\frac {y^{2}}{x^{2}} = {\frac {1}{4}} \]

3478

\[ {}\sin \left (x \right ) y^{\prime }+2 y \cos \left (x \right ) = 1 \]

3479

\[ {}\left (5 x +y-7\right ) y^{\prime } = 3 x +3 y+3 \]

3480

\[ {}x y^{\prime }+y-\frac {y^{2}}{x^{{3}/{2}}} = 0 \]

3481

\[ {}\left (2 \sin \left (y\right )-x \right ) y^{\prime } = \tan \left (y\right ) \]

3482

\[ {}\left (2 \sin \left (y\right )-x \right ) y^{\prime } = \tan \left (y\right ) \]

3483

\[ {}y^{\prime \prime }+{y^{\prime }}^{2}+y^{\prime } = 0 \]

3484

\[ {}x^{\prime \prime }+\omega _{0}^{2} x = a \cos \left (\omega t \right ) \]

3485

\[ {}f^{\prime \prime }+2 f^{\prime }+5 f = 0 \]

3486

\[ {}f^{\prime \prime }+2 f^{\prime }+5 f = {\mathrm e}^{-t} \cos \left (3 t \right ) \]

3487

\[ {}f^{\prime \prime }+6 f^{\prime }+9 f = {\mathrm e}^{-t} \]

3488

\[ {}f^{\prime \prime }+8 f^{\prime }+12 f = 12 \,{\mathrm e}^{-4 t} \]

3489

\[ {}f^{\prime \prime }+8 f^{\prime }+12 f = 12 \,{\mathrm e}^{-4 t} \]

3490

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 4 \,{\mathrm e}^{-x} \]

3491

\[ {}y^{\prime \prime \prime }-12 y^{\prime }+16 y = 32 x -8 \]

3492

\[ {}\frac {y^{\prime \prime }}{y}-\frac {{y^{\prime }}^{2}}{y^{2}}+\frac {2 a \coth \left (2 a x \right ) y^{\prime }}{y} = 2 a^{2} \]

3493

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = x \]

3494

\[ {}\left (1+x \right )^{2} y^{\prime \prime }+3 \left (1+x \right ) y^{\prime }+y = x^{2} \]

3495

\[ {}\left (x -2\right ) y^{\prime \prime }+3 y^{\prime }+\frac {4 y}{x^{2}} = 0 \]

3496

\[ {}y^{\prime \prime }-y = x^{n} \]

3497

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \,{\mathrm e}^{x} \]

3498

\[ {}2 y y^{\prime \prime \prime }+2 \left (y+3 y^{\prime }\right ) y^{\prime \prime }+2 {y^{\prime }}^{2} = \sin \left (x \right ) \]

3499

\[ {}x y^{\prime \prime \prime }+2 y^{\prime \prime } = A x \]

3500

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+6\right ) y = {\mathrm e}^{-x^{2}} \sin \left (2 x \right ) \]